A STUDY OF DRUG UTILIZATION PATTERN OF ANALGESICS IN POST-OPERATIVE PATIENTS IN A TERTIARY CARE HOSPITAL - Das, Daradi; Chakravarty, Pinaki; Borah, Dhrubajyoti; Yashin, Ali N (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of the study was to evaluate the utilization pattern of analgesic use in post-operative wards of different surgical specialties. Methods: The study was observational and retrospective conducted, for 4 months from November 2022 to February 2023 in Tezpur Medical College, Assam and data were collected from 80 patients’ case sheets regarding analgesics prescribed during post-operative days, their route of administration, mono/combined therapy. Results: Non-steroidal anti-inflammatory medications (NSAIDs) as diclofenac (55.5%) and paracetamol (32.5%) were commonly prescribed for relief, both in monotherapy and combination therapy. Tramadol, an opioid was also used for severe pain relief and then shifted to NSAIDs. All patients were prescribed injectable analgesics on the day of surgery and the 1st post-operative day. Combination of aceclofenac + paracetamol (7.70%) was the most prescribed oral analgesic followed by tramadol + paracetamol (3.50%), mostly prescribed as brand names. Conclusion: Diclofenac was the most used NSAID in post-operative pain both in mono and combined therapy and the prescribing pattern was not rational related to more use of brand names.